The ageing of society in the context of dominant assumptions of contemporary economics and culture - Michalski, Michał A. (Annales. Etyka w Życiu Gospodarczym, 2019)
Current demographic trends indicate that the process of ageing is more and more advanced in Western societies. While the available literature addressing this issue concentrates most often on developing effective tools for socio-economic policy, this paper aims at exploring the dominating assumptions of economics and culture to find how they may influence the demographic process that was mentioned. The purpose of the analysis undertaken here is to verify the thesis which claims that basic anthropological assumptions present in neoclassical economics and modern culture somehow ignore or underestimate such essential aspects of human life as old age and the helplessness or weakness connected with it. The conclusions of the paper indicate that there is a need for intergenerational balance within society, which, e.g., facilitates socio-economic development. Some of the most important factors influencing this may or may not be present within the economic theory and culture it is based on. It means that without the adequate vision of man and the phases of human life, the process of building a mentally healthy and vibrant society where everyone has his or her place is hardly possible.